1995
DOI: 10.1093/infdis/171.5.1081
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Double-Blind, Placebo-Controlled Trial of Systemically Administered Interferon- , - , or -  in Combination with Cryotherapy for the Treatment of Condyloma Acuminatum

Abstract: One hundred fifty-two patients were enrolled in a study to evaluate 3 interferon (IFN) preparations used in combination with cryotherapy for treatment of anogenital warts. Subjects received subcutaneous injections (2 x 10(6) units/m2) of IFN-alpha n1, -beta, -gamma or placebo 3 times a week for 6 weeks and cryotherapy with liquid nitrogen. Subjects were followed < or = 1 year. Among patients followed > or = 12 weeks, two-thirds had a complete response. No significant differences in rates of complete response (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…However, IFN-␣ has been shown not to affect outcome compared to placebo following CO 2 laser ablation (Condyloma International Study Group, 1993). Similarly, a study comparing IFN-␣, -␤, -␥ or placebo in combination with cryotherapy found no difference in response (Bonnez et al, 1995). Interferon therapy has never really gained a therapeutic niche.…”
Section: Photodynamic Therapymentioning
confidence: 99%
“…However, IFN-␣ has been shown not to affect outcome compared to placebo following CO 2 laser ablation (Condyloma International Study Group, 1993). Similarly, a study comparing IFN-␣, -␤, -␥ or placebo in combination with cryotherapy found no difference in response (Bonnez et al, 1995). Interferon therapy has never really gained a therapeutic niche.…”
Section: Photodynamic Therapymentioning
confidence: 99%
“…Two trials (n=137) investigated adjuvant beta-IFN in a high-dose5 and very high dose2 combined with an ablative therapy. No significant differences between the verum and placebo groups were seen for short-term CC (1 RCT, RR 0.88, 95% CI 0.45 to 1.73, GRADE: low) and intermediate-term CC (1 RCT, RR 1.22, 95% CI 0.95 to 1.56, GRADE: low), both of these referring to a very high dose regimen.…”
Section: Resultsmentioning
confidence: 99%
“…No significant differences between the verum and placebo groups were seen for short-term CC (1 RCT, RR 0.88, 95% CI 0.45 to 1.73, GRADE: low) and intermediate-term CC (1 RCT, RR 1.22, 95% CI 0.95 to 1.56, GRADE: low), both of these referring to a very high dose regimen. The RR regarding dropout due to AE could not be calculated due to zero events 5. Occurrence of AE showed no significant differences to placebo (see online supplementary material 2.4.2); these data refer to the high-dose regimen.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations